Use of analgesics in patients affected by head & neck malignancy during palliative radiotherapy - Simonida Crvenkova; Krstevska, Valentina; Kraleva, Slavica; Stojkovski, Igor; Stojmenova, Vita (My University, 2003)
Background: Treating the Head & Neck malignancy failure after surgery and radiotherapy (RT) is still a problem. The roles of reirradiation and chemotherapy are palliative. These patients (pts) suffered from moderate to sever pain that was less responsive to opioid therapy. The aim of this study was to evaluate efficiency among tramadol and amitriptyline in head & neck cancer pts with moderate pain during palliative RT. Material and Methods: 30 pts (21 M, 9 F) affected by head & neck metastatic disease in lymph nodes, failure after primary therapy. All pts included presented moderate pain defined as VAS between 5–7, and were under NSAIDs treatment and palliative RT. 15 pts (group A) used tramadol with initial dose 200 mg/day, with doses escalated up to 300-400/day. Other 15 pts (group B) used amitriptyline with starting dose 10 mg in the elderly and 25 mg in younger pts with doses increased every few days, when doses have reached the effective range (e.g. 75–100 mg). Pain was measured according the linear VAS (0-10) at the start of and during the period and at the end of RT, including day 0, 7, 14 and 21. Results: There was a difference between groups in VAS evaluation, this was: 6.2, 5.3, 4.8, 4.9 at days 0, 7, 14, and 21 respectively for tramadol group-A and 6.1, 3.5, 1.7, 1.2, respectively for group-B. Percentage of pts under pain control (VAS <3) was registered only in group B in follow up visits (40.6% at day 7, 80% at day 14 and 86.6 % at day 21). Conclusions: Tricyclic antidepressant-amitripyline was significant efficiency pain treatment in head & neck cancer pts with moderated pain. Considering our results, we supposed that there is distinct mechanism that created neuropathic pain in the head & neck region. available by spring 2003. 74P